(untitled) (Journal of the College of Basic Education, 2022)
This research aims to the relation between long period of infection with diabetes mellitus type 2 and some drugs that cause decrease lipids in serum blood and measure liver’s enzymes and study the relationship between formation stone in gallbladder and high level of cholesterol and triglyceride. the studied measurer levels of some Biochemical profile such as : (blood glucose , Glycosylate hemoglobin HbA1c , cholesterol, Triglyceride ,High density lipioprotein – cholesterol(HDL-C) ,low density lipioprotein- cholesterol(LDL-C), glutamic pyruvate transaminase enzyme(GPT),glutamic oxaloacetate transaminase enzyme(GOT), Alkaline phosphates enzyme )and measure of serum total protein ,Albumin , Globulin in patients infected with diabetes type2 before and after treatment for three years. Blood samples collected before and after three years infected and treated and the above mention parameters were measured as scheduled. This study contains (100) samples Diabetes patients un controlling glucose divided in to (50males , 50females ) and 50 healthy person divided in (25 males ,25 females )from the same area no infected with diabetes mellitus depended as a control group . The patients infected with diabetic treated by daonil and Metra famine and lipids drugs( Gemfibrozl (lopid 600). High levels in lipids profile for three years caused to stone in gall bladder in female group more than male group due to may be to relation between the infection with diabetes mellitus and length period infection with high level of cholesterol and triglyceride . It is clear that treatment of diabetes by lipids drugs caused decreasing in blood level profile, also liver founded in good function and high enzyme level induce to high level of cholesterol but no dangerous or risk about it due to infected with diabetes after three years. Blood glucose continuous with high level but don’t increase above before treatment that refers to patients not engagement with diet and sport exercises and the patients did not care about diabetes and complications.